Settlement of bad financing by one of the Sharia cooperatives through a simple lawsuit with property rights guarantee (No liens) in the Religious Court - Tidolaksono, Himawan; Sukresno, Sukresno (Journal of Law Science, 2024)
This study looks at how Sharia Cooperatives handle non-performing loans by filing a straightforward case in the Religious Court and securing a mortgage-free certificate of ownership. The following questions are part of the issue statement: (1) How can this cooperative resolve problematic finance legally? (2) What does the judge's ruling on funding with this assurance say in the Religious Court? A descriptive-analytical qualitative technique is used in this study. The data reveal that the procedure for resolving problematic financing consists of four parts: (1) kinfolk or discussion, (2) rescheduling, (3) collateral sale, and (4) litigation in religious courts. The procedure for lawsuit is governed by article 49 of Law no. 50 of 2009, which is an amendment to Law no. 3 of 2006 (i). To ensure the buyer's legal certainty and security, the sale of the collateral object must be conducted through the State Auction Office (KNL) in accordance with article 200 paragraph (1) HIR, if the certificate does not have a mortgage (HT) attached, as per the decision of the Religious Court. Part of the sale money goes toward paying off the defendant's debts to the plaintiff and covering the expenses of the auction and lawsuit. The other half goes back to the defendant. Findings from this study stress the need of creating sharia-compliant procedural legislation for religious courts to use when deciding sharia-compliant economic conflicts. The government and lawmakers are anticipated to promptly address procedural laws, while the Supreme Court has the authority to establish technical standards to bolster the responsibilities of religious courts.